Pengendalian Hama Terpadu: Pendekatan dalam Mewujudkan Pertanian Organik Rasional - Arifin, Muhammad (Puslitbang Tanaman Pangan, 2012)
In a strict organic farming, cultivation techniques rely on natural organic inputs, avoiding the use of synthetic chemicals, such as inorganic fertilizers and chemical pesticides. To implement such farming techniques many problems are faced by farmers such as in obtaining land which had not been contaminated by chemicals. Newly opened lands which are isolated from intensively cultivated area are very vulnerable to pests and diseases. Therefore, to attain food self-sufficiency, the right choice could be a rational organic farming applying Integrated Pest Management (IPM) approach. The rational organic farming allows the use of inorganic fertilizers along with the organic fertilizers in a balanced manner, and rational use of synthetic chemical pesticides as needed, based on food safety and ecology. The challenge is how to motivate farmers to produce organic fertilizers, biopesticides, and then to apply it in a system of rational organic farming.